Frozen in anxiety? On the experience of time in the stories of Polish women prisoners of camps and gulags - Kołodziejska, Agnieszka (Adam Mickiewicz University Poznan, 2023)
The Lager and Gulag experience is mainly known and discussed in the Polish school on the basis of male narratives (T. Borowski, G. Herling-Grudzinski). The article is based on long-overlooked female testimonies, which constitute extensive and necessary to take into account material of high source-informational as well as literary value. The author considers one element of a women’s camp experience, which is the sensation of time in a state of imprisonment: confinement in the confined and closely guarded space of a German concentration camp, a Soviet prison and a gulag located in the wilderness of the Russian North. She reflects on the individual and communal nature of the above experiences and their literary representation, situating them in light of the reflections of K. Jaspers, J. Leociak and psychiatrists dealing with post-camp trauma. Doświadczenie lagrowe i łagrowe znane jest głównie i omawiane w polskiej szkole na podstawie narracji męskich (T. Borowski, G. Herling-Grudziński). Artykuł oparty jest na długo niedostrzeganych świadectwach kobiecych, które stanowią obszerny i konieczny do uwzględnienia materiał o wysokiej wartości źródłowo-informacyjnej i literackiej. Autorka rozważa jeden z elementów kobiecego doświadczenia obozowego, jakim jest odczuwanie czasu w stanie uwięzienia: zamknięcia w ograniczonej i pilnie strzeżonej przestrzeni niemieckiego obozu koncentracyjnego, sowieckiego więzienia oraz łagru położonego na bezkresach rosyjskiej Północy. Zastanawia się nad jednostkowym i wspólnotowym charakterem powyższych doświadczeń i ich literackiej reprezentacji, sytuując je w świetle refleksji K. Jaspersa, J. Leociaka oraz psychiatrów zajmujących się poobozową traumą.